Modelling The Nexus Between Energy-Economic Growth Using The Long Panel Data Estimations - Sim, Khang Yi (2024)
This thesis examines a two-way causal relationship between energy consumption and economic growth for two panel groups, i.e., low and lower-middle-income economies (Group 1) and high-income economies (Group 2), over 1990–2019 with quarterly datasets. Apart from the first objective, this thesis aims to address various estimation issues related to long panel data that conventional panel models frequently overlook, covering nonstationary or cointegration, slope heterogeneity, cross-sectional dependence and dynamic effect.